Improving banks' profitability through income diversification and intellectual capital: The sub-Saharan Africa perspective - John Kwaku Mensah Mawutor; Isaac Boadi; Samuel Antwi; Anthony Buawolor Tetteh (Cogent Economics & Finance, 2023)
This study explores the impact of revenue diversification and intellectual capital on the performance of sub-Saharan African banks. The study applied a panel regression technique to a data set containing information on 80 banks from 21 countries from 2000 to 2020. Secondary data was collected from the unconsolidated financial statements of banks in the Bank scope database, WDI database, and Refinitiv database. The study utilized the two-step system GMM and the dynamic panel threshold regression estimation methods to evaluate the hypotheses. The study revealed that income diversification has a negative and significant impact on the profitability of banks in Sub-Saharan Africa. The study also indicated that value-added intellectual coefficient (VAIC), human capital efficiency (HCE), and structural capital efficiency (SCE) have a positive and significant effect on the performance of banks; however, capital employed efficiency (CEE) has a negative and significant impact on banks' profitability. The study also revealed that VAIC and HCE positively and significantly moderate the relationship between income diversification and the profitability of banks. SCE has a positive and insignificant moderating effect on the relationship between income diversification and bank performance. The study also revealed that CEE negatively and significantly mediates the relationship between income diversification and banks' profitability. The threshold results also provide evidence that VAIC and HCE positively affect profitability; however, VAIC and HCE affect profitability above the threshold value. We also found evidence of a threshold effect of SCE below the threshold and a negative effect above the threshold value. The study also revealed that CEE negatively affects banks' profitability at all levels. The detrimental impact of income diversification on the performance of sub-Saharan banks should be a concern for bank managers. The findings are crucial to comprehending the banking industry developments in Sub-Saharan Africa (SSA) from 2000 to 2020. The results provide important insights into the significance of the development of intellectual capital for the diversification of banking activities in SSA.
Keywords: 330; income diversification; intellectual capital; profitability and dynamic panel regression; two-step system generalized method of moments (GMM); value-added intellectual coefficient